GELAR KARAENG HAJI DAN STATUS SOSIAL PADA MASYARAKAT DESA TAMAONA KECAMATAN KINDANG KABUPATEN BULUKUMBA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The main problem in this study is how the community views the title of Karaeng haji and how is the social status of Karaeng haji in Tamaona Village, Kindang District, Bulukumba Regency. The purpose of this study was to determine the public's view of the title of Karaeng Haji and to determine the social status of "Karaeng Haji" in Tamaona Village, Kindang District, Bulukumba Regency. This type of research is descriptive qualitative with the approach used is a scientific approach to Hajj and Umrah management and a sociological approach. In this study, the authors used data collection methods through observation, interviews, and documentation. Data processing and analysis techniques go through four stages, namely data reduction, data display, comparative analysis and drawing conclusions. The results of the study show that the social status of people who hold the title of Karaeng haji has a striking difference in the eyes of the community. This is evidenced when there are events such as weddings, circumcision, religious events such as the birthday of the Prophet Muhammad. A person who holds the title is more respected and prioritized in these events. The public's view of the social status of Karaeng haji is that Karaeng haji is a status that has a special position in the eyes of the people of Tamaona Village. Because society emphasizes the importance of historical roots and views people who have made the pilgrimage to have more knowledge and wealth, this is the basis for justifying why they deserve to have a special position in society. However, not everyone agrees that people with the title of karaeng haji are given excessive respect, especially to the point that people think only people who have the title of karaeng haji deserve respect because after all we are all equal in the eyes of Allah swt. Not a few residents of Tamaona Village who hold the title of karaeng hajj and hajj who object if they are not called with that title because they understand that performing the pilgrimage is not just to get that title. The implication in the study is that based on the results of research conducted by researchers, it shows that the social status of people who hold the title of Karaeng haji in Tamaona Village is in line with existing theory, Owners of high social status will also be placed in a higher place in the community structure compared to owners of social status. The low one. The view of the Tamaona Village Community towards the title of Karaeng haji is in line with the existing theory. Their respectable community groups always emphasize the importance of historical roots which are the basis for justifying why they deserve to have a special position in society such as the title of Karaeng haji.